Early thrombocytopenia in HIV infection. Issue 9 (September 1992) - Beattie, R M; Trounce, J Q; Lyall, E G; Gibb, D M
Abstract : Three children aged between 7 months and 2 years developed thrombocytopenia as an early feature of HIV infection. The prevalence of this condition, possible pathogenesis, and options for treatment are discussed. HIV testing should be considered in the investigation of a child with thrombocytopenia.